Employing Microwave Graphene Field Effect Transistors for Infrared Radiation Detection - Antonio Benfante; Marco A. Giambra; Riccardo Pernice; Salvatore Stivala; Enrico Calandra; Antonino Parisi; Alfonso C. Cino; Simone Dehm; Romain Danneau; Ralph Krupke; Alessandro C. Busacca (IEEE Photonics Journal)
In this work, we investigate the possibility of employing graphene field effect transistors, specifically designed for microwave applications, as infrared detectors for telecom applications. Our devices have been fabricated on a sapphire substrate employing CVD-grown transferred graphene. The roles of both the gate dielectric and the DC bias conditions have been evaluated in order to maximize the infrared generated signal through an experimental investigation of the signal-to-noise ratio dependence on the transistor operating point.